Early results of different types of anorectoplasty for anorectal malformations - Rahman, Mizanur; Islam, Tarikul; Sharif, Zafor; Akhter, Most Dalia (Mediscope, 2021)
Objective: To document our experience with the technique of surgical repair in anorectal malformations (ARM) and the short term anatomical and functional outcomes. Methods: This study included total 31 babies. Fourteen were perineal fistula cases with age range between 1 to 4 days. Ten patients had vestibular fistula and seven had rectourinary fistula. Primary diverting colostomy was done for vestibular and rectourinary fistula patients. On the other hand low imperforate anus with anoperineal fistula without associated major anomalies had undergone fistulectomy and simple anoplasty. Results: Simple anoplasty was done for fourteen perineal fistula cases. Anterior sagittal anorectoplasty (ASARP) was done for 10 vestibular fistulae and posterior sagittal anorectoplasty (PSARP) was done in 10 recto-urinary fistula cases. Simple anoplasty and vestibular anus scored good (5-6) in 70% to 71% while PSARP scored fair in 58% of the cases. Postoperative mucosal prolapse, anal stenosis and retraction occurred in two, six and one patient respectively. Redo surgery was done in mucosal prolapse and retraction cases. Four responded to anal dilation and the other needed redo surgery by a simple cutback technique for anal stricture. Continence was assessed in 23 patients whose follow-up periods were longer than 3 years. Twenty one patients had a good score and two had a fair score. No patients had a poor score. Conclusion: Our approach has the following advantages: (i) The operative technique is simple and easy to perform. (ii) Minimal complication rate with good cosmetic results. Mediscope 2021;8(2): 75-79